Intervenção educacional em grupo para promoção do consumo de frutas e hortaliças de Agentes Comunitários de Saúde do município de Porto Feliz-SP - Alcalá Garcia, Carina [UNESP] (2014)
This intervention study assessed the impact of a group education activity on the consumption of produce (fruits and non-starchy vegetables) by community health agents from a small municipality in the state of São Paulo. The intervention group (n=16) consisted of agents who participated in five group sessions and a cooking workshop, and the control group consisted of agents (n=30) who did not participate in those activities. Produce intake in grams and percentage of total energy intake was investigated by one 24-hour dietary recall and two 24- hour food records(one weekday and one weekend day). The three instruments were administered before and 90 days after the intervention. The impact of the intervention was assessed by repeated measures analysis of variance (ANOVA) followed by the Tukey's test or gamma followed by multiple comparison test depending on variable distribution (symmetric or not). The chi-square test for trend compared the distributions of the individuals in the two groups before and after the intervention according to the stages of change of the transtheoretical model. The participants also assessed the intervention and its effect. The study also investigated the impact of the two groups on the produce intake of the families they visited. The data were treated by the software SAS for Windows version 9.3 with a significance level of 5% or corresponding p-value. The non-starchy vegetable intake (in grams and percentage of total energy intake) of the intervention group increased significantly, but not the fruit intake. The produce intake in grams and percentage of total energy intake also did not change. Sixty percent of the intervention group increased their produce intake against 25% of the control group. All participants in the intervention group reported positive repercussions associated with the intervention, citing greater awareness of the importance of healthy food habits most. The intervertion group ...